Tanggung Jawab Negara Memelihara Anak Terlantar Perspektif Negara Kesejahteraan.: State Responsibility in the Care of Abandoned Children: A Welfare State Perspective - Firman Octhaviana Sulistiyono; Aan Efendi; Al-Khanif Al-Khanif (UIN Kiai Haji Ahmad Sidiq Jember, 2025)
Article 34 paragraph (1) of the 1945 Constitution of the Republic of Indonesia states that